2010
DOI: 10.1021/ic901904b
|View full text |Cite
|
Sign up to set email alerts
|

An Iron-Based Cytosolic Catalase and Superoxide Dismutase Mimic Complex

Abstract: The development of metallodrugs with antioxidant activities is of importance as a way to protect organisms exposed to stressful conditions. Although iron chemistry in the presence of H(2)O(2) is usually associated with pro-oxidant activity, mainly via the Fenton reaction, we found that the mononuclear compound [Fe(HPClNOL)Cl(2)]NO(3) (1; C(15)H(18)Cl(3)FeN(4)O(4), a = 8.7751(3) A, b = 9.0778(4) A, c = 24.3869(10) A, beta = 93.370(2) degrees , monoclinic, P2(1)/c, Z = 4), containing the tripodal ligand 1-[bis(p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…The complexes had a much lower catalytic efficiency than native CuZn-SOD, which has an IC 50 value of 0.04 µM, 32 showed that all three complexes behaved as SOD and CAT mimics and the Fe(III) complex exhibited the highest protective effect, followed by Cu(II) and Mn(II). 33 In terms of the complexes acting as DNA nucleases, their ability to disproportionate H 2 O 2 to oxygen and water, would argue against these complexes being good nucleases. Reasonable catalase activity could only be recorded for complex 3 (Table 5), which was identified as the most cytotoxic compound.…”
Section: Determination Of Sod and Cat Mimetic Ability In A Cell-free mentioning
confidence: 99%
“…The complexes had a much lower catalytic efficiency than native CuZn-SOD, which has an IC 50 value of 0.04 µM, 32 showed that all three complexes behaved as SOD and CAT mimics and the Fe(III) complex exhibited the highest protective effect, followed by Cu(II) and Mn(II). 33 In terms of the complexes acting as DNA nucleases, their ability to disproportionate H 2 O 2 to oxygen and water, would argue against these complexes being good nucleases. Reasonable catalase activity could only be recorded for complex 3 (Table 5), which was identified as the most cytotoxic compound.…”
Section: Determination Of Sod and Cat Mimetic Ability In A Cell-free mentioning
confidence: 99%
“…Diabetic nephropathy is a severe, chronic complication of diabetes mellitus, and it is the leading cause of end-stage renal failure in diabetic patients [9]. It results from the combined effects of various genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…52,54,55 Complexes of both iron and copper exhibit superoxide scavenging activity, however these metal ions also exhibit pro-oxidant activity. [56][57][58][59] In contrast, manganese ions react poorly with hydrogen peroxide and do not generate the highly toxic hydroxyl radical, providing a beneficial antioxidant activity without the prooxidant side effects of other redox active metals. 50,60 It appears that Mn-antioxidants can serve to enhance oxidative stress protection when enzymatic antioxidants are insufficient in various organisms.…”
Section: Non-protein Manganese Antioxidantsmentioning
confidence: 99%